Was hat Athen mit Jerusalem zu tun?: Hugo Rahner, der antike Mythos und das frühe Christentum - Karmann, Thomas R. (Zeitschrift für katholische Theologie, 2019)
This paper examines the contribution that Hugo Rahner made to the study of Patristics, particularly by taking as an example his Greek Myths and Christian Mystery (first published in 1945). A first step will be to describe the circumstances in which it was written, while Rahner was exiled in Switzerland and took part at the Eranos conferences. A second step will be to describe the content of the book itself, in which Rahner shows himself to be no mere historian but also a theologian with a notable kerygmatic and pastoral focus, something which becomes particularly clear if in a third step one compares his book to more recent publications on this topic. In the face of dictatorships and war, Rahner sought to advocate for a genuinely Christian humanism. He dreamed of a »schöneres Abendland«. Jerusalem, Athens and Rome formed for him the inseparable foundations of Europe.